(untitled) (Research, Society and Development, 2022)
This article aims to discuss the problems of Brazilian education that, although they are not new, this view helps to understand more clearly the poor Brazilian performance in educational tests, such as PISA and SAEB. To this end, we used the bibliographical research whose notes have already been widely disseminated by the Brazilian academy, either by university professors, by basic education teachers, union instances and/or the main stream media. Therefore, we also observed that several of these "problems" have been re-signified or neglected over the decades. Thus, we started from the most common arguments used to justify such a low placement to Brazil in these rankings (coming behind less developed countries), such as: the low investment in education in Brazil, school indiscipline and its consequences for teachers, the low stimulus of attraction for the younger generations, the modification that the teaching career has been going through and, above all, the discourses that support these changes, to base ourselves to understand what would be the crux matter. Finally, we observed that although the problems are intrinsic to education and have names and surnames, the biggest conflict is in the different visions of how to solve them. In this way, we noticed ample discussions and visions about such problems, however, in what concerns about praxis and which attitudes should or could be taken, nothing concrete is elaborated or established. We hope that this article will contribute to clarify the points mentioned, which have been widely discussed, but are far from consensus.